Social Impacts of Organizing Cultural and Historical Streets: A Case study of Lalehzar Street - Hadi Barghamadi; Masoomeh Mohaghegh Montazeri (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2020)
Today, urban development programs because of the divergence of social, political and economic influences existing in the territorial dominions, have little control over the components and forces that shape urban spaces; So that the processes of power in the Metropolitan Area have led to the gradual elimination of unorganized groups and interests in favor of the dominant groups. In the Mashhad Metropolitan Area, despite the existence of regional, district and urban programs with the aim of a balanced organization of space and achievement of spatial justice, there are regional and urban imbalances, and the capital and power are highly centralized.  In consequence, the processes resulting from unlimited development have contributed to environmental degradation, migration of villagers to the city, increased urban squatter settlement and consequent damages. Undisputed political power by the means of powerful political, economic and social tools, has been the main element in determining the space organization and has regulated and directed the actions of public and private sectors. The present study is developmental in nature and is based on a mixed methodology, using a questionnaire of experts, and applying CFA factor analysis model in identifying the power and influence of contributing factors in spatial structuring and their relationships, goals and intentions. The findings of the current study showed that the elements of power of sovereignty, government, public sector and citizens have had the most influence on shaping the spatial organization of Mashhad Metropolitan Area, respectively.